PEDAGOGICAL PROBLEMS OF FORMING A HEALTHY LIFESTYLE IN PRIMARY SCHOOL STUDENTS - Karasartova J. B.; Usonakunova G. M. (Vestnik Issyk-Kulʹskogo universiteta, 2025)
This article addresses the pedagogical problems of forming a healthy lifestyle among primary school students. Based on the theories of several scholars, the author emphasizes that the tasks and principles of developing healthy lifestyle habits in children are relevant and significant in the modern education system. Special attention is paid to the fact that health and a healthy lifestyle play a key role in the process of shaping children’s personalities and improving their living conditions. The article clarifies basic concepts related to health and provides definitions concerning the health issues of primary school students in the context of their upbringing. The author proposes organizing a series of targeted activities aimed at forming the pedagogical foundations of children’s personalities during the process of fostering a healthy lifestyle. One of the pedagogical foundations of this process—methods of strengthening health used in the modern education system—is also discussed. The article outlines the main requirements for educating primary school students in the spirit of a healthy lifestyle. It highlights the necessity of considering the specifics of the content and nature of educational activities for primary school students, regulating the psychological intensity of their voluntary activities, and ensuring an optimal level of their motor and physical performance.